The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fspas.2022.878653
|View full text |Cite
|
Sign up to set email alerts
|

Five Dimensional Bianchi Type-I Anisotropic Cloud String Cosmological Model With Electromagnetic Field in Saez-Ballester Theory

Abstract: Within the context of Saez-Ballester theory, we explored the interaction of a five-dimensional Bianchi type-I anisotropic cloud string cosmological model Universe with an electromagnetic field. With an electromagnetic field, the energy momentum tensor is assumed to be the sum of the rest energy density and string tension density in this paper. We use the average scale factor as an integrating function of time to get exact answers to Saez-Ballester equations. The dynamics and importance of the model’s many phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…The anisotropy parameter behaves the same as model 4 − 20(cosh(at)) 2 (sinh(at)) 2 − 15(cosh(at)) 4 (cosh(at)) 4 (50)…”
Section: Physical Aspects Of the Modelmentioning
confidence: 93%
See 2 more Smart Citations
“…The anisotropy parameter behaves the same as model 4 − 20(cosh(at)) 2 (sinh(at)) 2 − 15(cosh(at)) 4 (cosh(at)) 4 (50)…”
Section: Physical Aspects Of the Modelmentioning
confidence: 93%
“…Lerk parameter l (t) = 76(sinh(at)) 4 − 180(cosh(at)) 2 (sinh(at)) 2 + 105(cosh(at)) 4 (cosh(at)) 4 (51)…”
Section: Physical Aspects Of the Modelunclassified
See 1 more Smart Citation
“…In contrast to the latter, the SB theory includes the action of ordinary matter that is not coupled to the SB scalar field. Various cosmological models have been established in the context of the SB theory to study open problems in both the classical and quantum regimes [49][50][51][52][53][54]. Applying the similar reduction procedure used to construct the MBDT, without assuming the presence of the higher dimensional matter fields and imposing the cylindricity condition on the extra coordinate, it has been shown that the SB field equations associated to the bulk split into four sets of effective field equations on any hypersurface orthogonal to the extra dimension [9].…”
Section: Introductionmentioning
confidence: 99%
“… 53). We note that in deriving the total energy density, we have used Equations (4.34), (4.35) and (4.46)-(4.49).…”
mentioning
confidence: 99%